Extreme Weather and Grazing Management Influence Soil Carbon and Compaction - Anish Subedi; Dorcas Franklin; Miguel Cabrera; Subash Dahal; Dennis Hancock; Amanda McPherson; Lawton Stewart (Agronomy, 2022)
Understanding the influence of cattle grazing on soil carbon and bulk density during extreme dry to wet periods can help us design more resilient and sustainable grazing systems for low-input management scenarios. A study was conducted to evaluate changes in loss-on-ignition (LOI) carbon and bulk density (BD) in the top 20 cm soil layer when eight continuous grazing (CG) pastures were converted to either continuous grazing with hay distribution (CHD-4) or strategic grazing (STR-4). STR included lure management of cattle with movable-equipages, exclusion and over-seeding erosion-vulnerable areas, and a relaxed rotational grazing. Changes in relationships between cattle density (CD), LOI, and BD were evaluated for change in grazing management from 2015 to 2018. Reduction in LOI carbon (0–5, 5–10, 10–20 cm) and BD (5–10 cm) were observed in both CHD and STR pastures in 2018. CD in 2015 had either no relationship or a negative relationship on LOI while in 2018, CD positively influenced LOI in CHD (0–5 cm) and STR (0–5 and 5–10 cm) pastures. STR had lower BD with higher CD further away from concentrated flow paths mirroring cattle movement. Exclusions in the STR pastures had the greatest reduction in BD. Even with reduced carbon in the 0–5 cm soil layer the reduction in BD in the 5–10 cm soil layer helped build resilience in grazing systems that experience extreme weather events such as going from very dry to extensively wet.